RNAi‐mediated silencing of the autophagy‐related gene NlATG3 inhibits survival and fecundity of the brown planthopper, Nilaparvata lugens. Issue 10 (22nd June 2021) - Ye, Chenglong; Feng, Yalin; Yu, Feifei; Jiao, Qiqi; Wu, Jiangen; Ye, Zihong; Zhang, Pengjun; Sun, Chuanxin; Pang, Kun; Hao, Peiying; Yu, Xiaoping
Abstract: BACKGROUND: The brown planthopper (BPH), Nilaparvata lugens, is a serious insect pest of rice. Autophagy and its related gene ATG3 play multiple roles in insects. However, information about the functions of ATG3 in BPH ( NlATG3 ) is unavailable, and its potential as a target for pest control remains unclear. RESULTS: RT‐qPCR results showed a relatively low expression of NlATG3 in 1st–4th‐instar nymphs, which increased through 9‐day‐old adults. The expression of NlATG3 increased continuously in 1‐day‐old through 5‐day‐old eggs, whereas it decreased thereafter. The mRNA level of NlATG3 was markedly higher in the ovary (1.16) and head (1.00) compared to the rest body parts of BPH adults. Injecting nymphs with dsNlATG3 at doses from 62.5 to 250 ng per insect had strong lethal effect upon them. For the 5th‐instar nymphs, all individuals died within 5 days after receiving the dsNlATG3, and importantly, no individual successfully molted. Transmission electron microscopy revealed the new cuticle of nymphs injected with dsNlATG3 became loose and curved, which is clearly different from that of the control. Correspondingly, the obvious vesicles in epidermal cells disappeared after dsNlATG3‐treatment. RNAi of NlATG3 significantly reduced the total number of eggs laid per female as well as the eggs' hatchability, especially in the dsNlATG3♀ × dsGFP♂ group, whose total number of eggs laid per female largely decreased by 80.4%, and whose eggs' hatchability was significantly reduced from 95.7% to zero, when compared with the control (dsGFP♀ × dsGFP♂). CONCLUSION: NlATG3 is a promising target for developing RNAi‐based insect management strategies. © 2021 Society of Chemical Industry. Abstract : RNAi of dsNlATG3 had strong lethal effects upon the nymphs and largely reduced the number of eggs and hatchability. NlATG3 is a promising target for developing RNAi‐based insect management strategies.